2022
DOI: 10.1186/s12960-022-00708-1
|View full text |Cite
|
Sign up to set email alerts
|

What makes community health worker models for tuberculosis active case finding work? A cross-sectional study of TB REACH projects to identify success factors for increasing case notifications

Abstract: Background In the field of tuberculosis (TB), Community Healthcare Workers (CHWs) have been engaged for advocacy, case detection, and patient support in a wide range of settings. Estimates predict large-scale shortfalls of healthcare workers in low- and middle-income settings by 2030 and strategies are needed to optimize the health workforce to achieve universal availability and accessibility of healthcare. In 2018, the World Health Organization (WHO) published guidelines on best practices for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The supportive supervision method was mentioned several times in articles [ 24 , 33 , 36 , 38 , 40 , 48 , 49 , 52 , 57 , 62 , 64 , 66 , 71 73 ] with promising results. Supportive supervision is an accommodative and facilitative process where supervisors facilitate solutions for problems not only those related to medicine or public health, but also any social and psychological issues.…”
Section: Resultsmentioning
confidence: 99%
“…The supportive supervision method was mentioned several times in articles [ 24 , 33 , 36 , 38 , 40 , 48 , 49 , 52 , 57 , 62 , 64 , 66 , 71 73 ] with promising results. Supportive supervision is an accommodative and facilitative process where supervisors facilitate solutions for problems not only those related to medicine or public health, but also any social and psychological issues.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, as both our study and others from resource-constrained settings have identified, community health workers must be adequately trained, protected and compensated, as they carry out this work. 37 Finally, our study highlights how, depending on its application and quality, information technology can both hinder and help TB care providers across the cascade of care. Shigatse lacks comprehensive and interoperable information technology platforms that span the health system.…”
Section: Open Accessmentioning
confidence: 89%
“…Indeed, as both our study and others from resource-constrained settings have identified, community health workers must be adequately trained, protected and compensated, as they carry out this work. 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a growing body of literature on scaling up community-based TB interventions recognizes the contribution of both formal and community health systems factors to their success [19,20]. In particular, several studies have shown that community health workers improve tuberculosis case detection [21,22], and treatment success whilst strong investment in TB diagnostic equipment has similarly contributed the improved treatment success in most countries.…”
Section: Introductionmentioning
confidence: 99%